IGFBP-1 marker of cervical ripening and predictor of preterm birth - Larisa Mešić Ðogić; Dragana Mićić; Feđa Omeragić; Refka Kovač; Seid Fazlagić (Medicinski glasnik, 2016)
Aim: To establish a correlation between positive values of IGFBP-1 (>10 mg/L, Actim Partus Test, APT) and premature cervical ripening in imminent preterm labor. Methods: A prospective study was conducted in primary health care centers in Tuzla, Gynecology and Obstetrics Clinic of the University Clinical Centre in Tuzla and General Hospital Tešanj. The study included 50 women (singleton pregnancy, 28-37 week) with imminent preterm labor diagnosed by cervical biometry and modified Bishop score) (examinees) and 30 healthy pregnant women (control group). The presence of IGFBP-1 was tested in cervical secretion several times in weeks 28-37 until a positive test was shown. Results: IGFBP-1 was positive in 43 (86%) examinees and in six (20%) patients from the control group (p=0.001). In 31 (62%) examinees APT was positive in weeks 28-30, and in nine (18%) in weeks 31- 33, while three (6%) examinees had positive test in 34-37 week; in the control group, three (10%) were tested positive in weeks 31-33 and three (10%) in weeks 34-37. At first testing (28-30 weeks) APT was statistically significantly more frequently positive in the examined group (p<0.05). Later, tests did not find statistically significant difference in the frequency of positivity between the control and examined group (p=0.08). Conclusion: Elevated values of IGFBP -1 in cervical secretion were highly correlated with preterm labor. Screening for IGFBP could help in preventing preterm labor and its complications.
Keywords: insulin-like growth factor binding proteins; premature birth; cervix mucus